2013
DOI: 10.1111/jfs.12085
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Antifungal Fractions from the Plants Baccharis glutinosa and Jacquinia macrocarpa on Chitin and β‐1,3‐Glucan Hydrolysis of Maize Phytopathogenic Fungi and on the Fungal β‐1,3‐Glucanase and Chitinase Activities

Abstract: Baccharis glutinosa and Jacquinia macrocarpa are medicinal plants whose antifungal activity has been observed on maize phytopathogenic fungi. However, the specific site where those compounds act has not been studied. The objective of this work was to evaluate the hydrolytic effect of antifungal fractions from B. glutinosa (BgF) and J. macrocarpa (JmF) on β-glucan and chitin isolated from Aspergillus flavus and Fusarium verticillioides, as well as their inhibition activity on the fungal hydrolases β-glucanase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Studies have shown that the content of chitin in edible fungi decreases due to the effect of chitinase in the storage process. Chitinase hydrolyzes the beta-1, 4-glycoside bond in chitinol to produce n-acetylglucosamine oligomer or monomer (Buitimea et al, 2013). Lim & Choi (2009) found that the Agaricus bisporus could produce black juice in the process of autolysis at 25 • C for 15 h. By PCR confirmed that the amount of chitinase synthesis in the process of autolysis of A. bisporus mushroom was significantly higher than that in the normal A. bisporus mushroom.…”
Section: Cell Wall Metabolism-related Enzyme Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that the content of chitin in edible fungi decreases due to the effect of chitinase in the storage process. Chitinase hydrolyzes the beta-1, 4-glycoside bond in chitinol to produce n-acetylglucosamine oligomer or monomer (Buitimea et al, 2013). Lim & Choi (2009) found that the Agaricus bisporus could produce black juice in the process of autolysis at 25 • C for 15 h. By PCR confirmed that the amount of chitinase synthesis in the process of autolysis of A. bisporus mushroom was significantly higher than that in the normal A. bisporus mushroom.…”
Section: Cell Wall Metabolism-related Enzyme Activitymentioning
confidence: 96%
“…During postharvest storage of edible fungi, changes in cell wall structure and composition directly contribute to cell separation, resulting in loose organizational structure and decreased hardness of fruiting body and, finally, decreased storability of edible fungi (Zivanovic, Buescher & Kim, 2003;Qi et al, 2015). Studies have addressed that the content of chitin decreased during postharvest storage due to the effect of chitinase by hydrolyzing the β-1, 4-glycoside bond in chitin and producing n-acetylglucosamine oligomer or monomer (Buitimea et al, 2013;Jiang et al, 2010a;Jiang et al, 2010b). Lim & Choi (2009) revealed that the Agaricus bisporus could rapidly produce black juice at 25 • C for 15 h after harvest and confirmed that the amount of chitinase synthesis in the autolysis process was significantly higher than that of unpicked mushrooms.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the essential oil concentration on the antifungal activity on F. oxysporum FCHJ-T6 and FCHA-T7 and F. equiseti FCHE-T8 was determined using the previously reported poisoned food technique [28][29][30]. The essential oil was incorporated into the sterilized and cooled PDA (~50 • C) at the proportions required to reach 0.1 mg/mL, 0.2 mg/mL, 0.4 mg/mL, 3 mg/mL, 5 mg/mL, and 8.4 mg/mL of medium and was poured into sterile 50 mm diameter Petri dishes.…”
Section: Poisoned Food Assaymentioning
confidence: 99%
“…b-1,3-Glucanases enzymatic assay b-1,3-Glucanase extracts were prepared in flasks containing 20 mL of Czapek broth, which were separately inoculated with 1 9 105 spores/mL of A. parasiticus and incubated for 96 h at 28 °C. The cultures were centrifuged, sonicated, and the supernatants were obtained following the procedure reported (Buitimea-Cantu ´a et al 2013).…”
Section: Morphometric Analysis Of Sporesmentioning
confidence: 99%
“…The effect of either CS nanoparticles or CS-LZ BNCs on the b-1,3-glucanase activity of A. parasiticus was determined by the production of reducing sugars, using 12 lL of the supernatant, 125 lL of laminarin 2.5% as substrate (Sigma-Aldrich, USA), 10 lL of bovine serum albumin (BSA, Sigma-Aldrich), and 362 lL of 50 mM sodium acetate buffer, pH 5.2. The mixture was incubated for 25 min at 37 °C and reducing sugars were estimated at 610 nm following the Somogyi-Nelson method using a standard curve of glucose (Buitimea-Cantu ´a et al 2013).…”
Section: Morphometric Analysis Of Sporesmentioning
confidence: 99%